HUKUM PIDANA ADAT SUB-CULTURE KEHIDUPAN HUKUM DI INDONESIA - Pujiyono pujiyono (Faculty of Law, Universitas Diponegoro, 2011)
Law as a weergave (refiection) in a society lives and created by the society itself therefore the iaw in society becoming the refiection of socio-phiiosophic values mf society itself. Indonesian society has its characteristics of being communal, social-religious and prioritizing the harmony of society hence here the life of Indonesian Law automatically imbued by those values. Indonesian Customary Law is the law that created and desired by the Indonesian society itself based on the value of its socio-phiiosophic to regulate the life of society, nation, and state. The existence of customary law characterized as rooted, paculier and society-based, means the customary law lives and develops in accordance to the values of the society and can not be replaced since it is the spirit and the will of society. The Dutch Law shifted and turned the customary (customary criminal) law off. The characteristic differences caused the discrepancy or the value gap occured. The customary criminal law has its characteristics such a) comprehensive and unifying; b) is opened; c) differentiating the probiems; d) justice by request and e) actions in the form of reaction or correction. Substantially, the customary criminal law has several differences to the Criminal Code, they are: according to the Criminal Code there will be a certain person only that can be convicted, meanwhile on the customary criminai law not only a person but law firm and the actor's family can also be asked for taking responsibilities. According to Criminai Code a person can only be convicted if the actions the person did were having the element of accident or negligence, while in the customary criminai law, the element of error is not an absolute element; on the Criminal Code been known and distinguished between assistance, persuade and participated in a crime, for which is unknown in the customary criminal law. All who took part against the rules of customary law are required to be accounted for; in the customary criminai law doesn't recognize the trial term, as its reulated in the Criminal Code; Criminal Code based on the system ofprae-exsistence regels while the customary criminal iaw doesn t; the customary iaw doesn t differentiate between civil law and criminal law; Criminal Code has its pattern as being intellectual and rational while in the other hand the customary criminal law has its base on cosmic think and prioritizing the harmony of society. The application of customary criminal law in the process of criminal justice having its base on the Act No. 1 Year1951 concerning Temporary Actions to Organize Events Unitary Structure of Power and Civil Courts, Article 5 paragraph (3) sub b. Institutionalization of customary criminal law in the life of the Indonesian national law occurs through three tracks, namely the judicial track, legislation track, and academic track. Kata kunci: Hukum Pidana Adat, Sub Culture Kehidupan Hukum Indonesia